Analisis Faktor-faktor yang Mempengaruhi Pendapatan Nelayan Buruh di Sepanjang Muara Sungai Ijo Gading Kabupaten Jembrana - Dewi, Ida Ayu Sukma; Rustariyuni, Surya Dewi (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 3, No. 1, Januari 2014 (pp. 1 - 47), 2014)
14.00 Fisherman is very depend on natural condition in conduct their economic acitivity. Economic activity has been arise stratitification in fisherman community and they occupy at the lowest level. This study aims to find out the difference of their income at fish season and less-fish season and to find out the effect of the amount of responsibility, working hour, age and distance go to the sea, toward coolie fisherman’s income at estuary area of Ijo Gading river, Jembrana. This study was quanititave. This study was applied purposive sampling by number of sample were 60 respondents. The data analyzed with multiple regression analysis.The result show there was significant difference between coolie fisherman’s income at fish season and less-fish season. There was significant effect among the amount of responsibility, working hour, age and distance go to the sea, toward coolie fisherman’s income at estuary area of Ijo Gading river, Jembrana regency. But partially only age and distance of go the sea have signifinicant effect. Normal 0 false false false EN-US X-NONE X-NONE
Keywords: nelayan buruh; pendapatan; jumlah tanggungan; jam kerja; usia; jarak tempuh melaut